Empowering Leadership and Employee Creativity: The Mediating Role of Psychological Empowerment - A Nuzul, A; Witjaksono, Andree Dwijanto; Kistyanto, Anang (SEISENSE Journal of Management, 2020)
Purpose: This paper tried to examine the mediation effect of psychological empowerment between empowering leadership and employee creativity Design/Methodology: This study referred to quantitative research design and used a paper-based online questionnaire to collect data from a sample of 65 employees drawn from an Information Technology company in Surabaya, Indonesia. This study used the SEM (Structural Equation Modeling) Partial Least Square analysis with saturated samples. Findings: The results indicate that empowering leadership and psychological empowerment positively and significantly affect employee creativity. The results further reveal that psychological empowerment significantly mediating the relationship between empowering leadership and employee creativity. Practical Implications: The findings of this study provide benefits for company leaders to identify learning solutions to practical solutions, motivate employees to come up with creative ideas, and empower employees. Mostly during challenging times such as during the COVID 19 pandemic, work must be done from home. The results of this study provide opportunities for leaders to produce techniques, policies, and strategies to increase employee creativity through motivation, direction, and empowerment Originality/Value: This study makes a new attempt to demonstrate the mediating effect of empowering leadership and employee creativity in Information Technology companies at Vascomm Surabaya Indonesia. In addition, the research underlines the importance of motivating and always giving employees freedom for creative behavior which is important knowledge in difficult times like today caused by the covid-19 pandemic.